2015
DOI: 10.11622/smedj.2015068
|View full text |Cite
|
Sign up to set email alerts
|

Optimal head rotation and puncture site for internal jugular vein cannulation after laryngeal mask airway insertion

Abstract: INTRODUCTIONRecently, the laryngeal mask airway (LMA) is frequently used for patients under general anaesthesia.(1-7) Occasionally, a clinical situation that requires internal jugular vein (IJV) cannulation after LMA insertion is encountered, especially for difficult airways in patients undergoing major surgery. (8,9) However, the anatomic relationship of the IJV and the common carotid artery (CCA) has been reported to change significantly in patients after LMA insertion.(10) The degree of overlap between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They found a higher overlap percentage and lower success rate of the simulated IJV cannulation after laryngeal mask airway vs ETT insertion. The cannulation of right IJV was considered to be more difficult after laryngeal mask airway insertion and Kim et al (16) explained this finding due to the displacement of the sternocleidomastoid muscle that makes the central landmark less valuable for IJV puncture and palpating the CCA more difficult. The results of our study also reveals similar results but in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a higher overlap percentage and lower success rate of the simulated IJV cannulation after laryngeal mask airway vs ETT insertion. The cannulation of right IJV was considered to be more difficult after laryngeal mask airway insertion and Kim et al (16) explained this finding due to the displacement of the sternocleidomastoid muscle that makes the central landmark less valuable for IJV puncture and palpating the CCA more difficult. The results of our study also reveals similar results but in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…One recent report compared the overlap of the CCA by the IJV after laryngeal mask airway and ETT placement in 100 adult patients under 15°, 30°, and 45° head rotation . They found a higher overlap percentage and lower success rate of the simulated IJV cannulation after laryngeal mask airway vs ETT insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Takeyama et al ( 7) reported a similar result in adults; one possible reason is that when the head rotated after LMA insertion, the CCA tends to be subject to external pressure from the inflated cuff, causing it to lean toward the dorsal side of the IJV. Furthermore, the LMA insertion may displace the sternocleidomastoid muscle, which makes palpating the CCA difficult (20). So, the usual attempts to catheterize the IJV just lateral to the CCA may result in failure.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although, studies have also proven the LMA insertion instigated the overlapping of IJV over CCA and distortion of anatomical land marks. 5 We present a case of difficult right sided IJV access under LMA anesthesia, which triggered the surgical morbidity like prolonged surgical duration and excessive blood loss.…”
Section: Introductionmentioning
confidence: 99%